Optimisation of a linear flow channel reactor for semi-passive, simultaneous biological sulphate reduction and partial sulphide oxidation - Fernandes, Sarah (Centre for Bioprocess Engineering Research, 2022)
Acid rock drainage (ARD) is a growing concern, particularly in South Africa, as a country already classified as water scarce. ARD is defined as water that has been impacted by mining activities and typically has high levels of sulphate and heavy metals, at acidic pH. Similarly, high sulphate neutral rock drainage is of increasing concern. High sulphate content increases water salinity leading to adverse effects on human health as well as agriculture. Types of ARD and neutral rock drainage can be categorised into those that are produced in high volumes from groundwater rebound, and those that are generated from diffuse sources, as low-flow ARD. Low-flow ARD and neutral rock drainage are amenable to biological treatment of the sulphate component using sulphate reducing bacteria (SRB). Biological sulphate reduction (BSR) generates sulphide, which requires further treatment to remove it from the stream in gaseous form or as a solid sulphur-containing compound. Alternatively, it can also be used, in part, to precipitate metals present within ARD waters. Key challenges associated with SRBbased bioremediation include the cost of the supplemented electron donor needed for SRB to reduce sulphate, as well as the downstream management or treatment of the excess sulphide remaining. This investigation aimed to optimise a semi-passive treatment process which integrates BSR, and concomitant partial oxidation, by sulphur oxidising bacteria (SOB), of the sulphide produced to elemental sulphur. This is generated as a floating sulphur biofilm (FSB). These processes occur simultaneously within a linear flow channel reactor (LFCR), facilitating both treatment of the water stream to a fit-for-purpose water product, and recovery of the sulphur for use within fertilisers or fungicides. The work focused on the effective utilisation of electron donors and a sustainable option thereof, as well as the optimisation of partial sulphide oxidation and sulphur recovery. In addressing the cost of a supplemented electron donor, the use of a waste product is of interest. To explore this and build on earlier work within the Centre for Bioprocess Engineering Research (CeBER) labs, this study investigated the efficient use of the volatile fatty acids (VFAs) acetate, propionate and lactate. Firstly, the study investigated propionate, a common fermentation product of waste organic sources. It is found as a component of the effluent or digestate, of anaerobic digestion (AD) processes such as algal AD. Propionate was proposed as an attractive option for a sustainable source of electron donor. An LFCR fed with synthetic propionate showed sulphate reduction occurring via the utilisation of both propionate as well as acetate produced from propionate metabolism. Fermentative bacteria were seen to work syntrophically within the system availing a significant amount of acetate to the SRB community. This acetate was the preferred electron donor over propionate. Maximum volumetric sulphate reduction rates (VSRRs) of 190 mg/L/day were achieved in the reactor. However, detailed analysis showed few propionate-utilising SRB in the community. It was concluded that a more diverse inoculum was needed to investigate the potential of propionate more fully. Secondly, the study investigated lactate as a means to explore the efficiency of electron donors that are incompletely oxidised to acetate. Higher chain VFAs such as lactate are partially oxidised to acetate under biosulphidogenesis; however, acetate oxidation by SRB appears to be a rate-limiting step in most systems. Simultaneous incomplete oxidation of the more complex VFAs with complete oxidation of acetate are rarely reported. Acetate accumulates in the effluents of these processes and results in high chemical oxygen demand (COD) remaining which can lead to environmental impacts such as eutrophication if released into river systems. Further, utilisation of the electron donor is inefficient. In order to address this, the study presents a sequential LFCR system to increase utilisation efficiency of the incompletely oxidised VFA feed. The sequential system was developed by coupling a second reactor unit, specifically colonised with acetate-utilising SRB, to a primary reactor unit utilising lactate. The SRB community in the secondary reactor was able to oxidise acetate from the primary reactor resulting in further sulphate reduction and lower residual COD levels. Residual acetate decreased from 475 mg/L in the primary reactor to 275 mg/L in the secondary reactor. Similarly, residual sulphate decreased from 533 mg/L in the primary reactor to 150 mg/L in the secondary reactor, on a 1 g/L sulphate feed, achieving a much improved effluent water quality. A VSRR of 213 mg/L/day across the sequential system, an overall conversion of 85% and a two-fold increase in sulphate reduced / lactate consumed from 0.45 to 0.85 (g/g) were achieved. Lastly, this study investigated sulphide removal via the incorporation of elemental sulphur into a floating sulphur biofilm (FSB). The generation of an FSB within a sulphate reducing bioreactor is a passive and sustainable method of sulphide remediation, producing a value-added product of elemental sulphur. The sequential reactor system resulted in an increase of two to three-fold in the amount of elemental sulphur recovered, with an improved conversion of sulphide formed to elemental sulphur. Further, the effect of the feed inorganic ions, magnesium and phosphate, on sulphur yield and sulphide removal was studied using the sequential LFCR system. It was found that a decrease of magnesium in the media supplied resulted in an increase in sulphide conversion to sulphur from 21 to 39%, while a concomitant reduction in feed phosphate resulted in a further increase to 50% of the same. In both cases the sulphur concentration in the FSB was substantially increased. Overall, the thesis addresses the need to decrease the cost associated with the supply of a suitable electron donor, as well as improves the water quality of a BSR effluent both in terms of residual sulphate, sulphide and COD. The LFCR system studied was improved both by a sequential reactor system, allowing greater sulphate reduction, sulphide removal via elemental sulphur recovery, and substrate utilisation efficiency. Additionally, changes to the inorganic component of the feed led to further sulphide removal and elemental sulphur recovery. Propionate was concluded to have been only partially used as an electron donor for SRB, however fermentative bacteria present in the mixed community degraded propionate to acetate which was then used for BSR. The work presented here contributes towards the broader research into a semi-passive, environmentally sustainable and economically viable treatment solution for low-flow, circumneutral ARD.